Museum exhibition marketing strategy: a case study of the Malaysian Islamic Art Museum / Muhamad Amirul Hafiz Zulkifli, Mohd Syuhaidi Abu Bakar and Nor Azlin Hamidon - Hafiz Zulkifli, Muhamad Amirul; Abu Bakar, Mohd Syuhaidi; Hamidon, Nor Azlin (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2019)
This study was conducted to examine the marketing strategies used by the management of the Malaysian Islamic Art Museum, Kuala Lumpur and to evaluate the effectiveness of marketing strategies used to attract visitors to the Malaysian Islamic Art Museum. A qualitative approach was employed and interview sessions were conducted to gain an overview of the marketing strategies applied by the museum. Interview instruments and bookcases were used to answer the objectives of the study which were to: (1) identify marketing strategies implemented by the management of the Malaysian Islamic Art Museum, Kuala Lumpur and (2) analyze the marketing strategies used to attract visitors to the museum. The findings concluded that the museum’s management has applied the 4Ps of mixed marketing theory that details product, price, promotion and place.